Statistical reasoning through metacognitive brain-based learning - Wati Susilawati; Ridha Abdullah; M N Abdullah (Department of Mathematics Education, UIN Sunan Gunung Djati Bandung, West Java, Indonesia, 2020)
The low ability of students' statistical reasoning needs a promising learning innovation. The aim of this paper is to evaluate students' learning abilities through brain-based learning with metacognitive strategy. The Quasi Experiment Method, Nonequivalent Pretest-Posttest Control Group design, involved a sample of two classes of third semester students from Gunung Djati Swadaya University Cirebon. Instruments of this paper are statistical reasoning test and statistical preliminary knowledge tests. The result shows an increase in the ability of statistical reasoning among students who conducted brain-based learning with metacognitive strategy in the smart category, higher than students who applied expository learning strategy that only classified as the moderate category. Based on initial statistical knowledge (low, middle, and high) students who applied brain-based learning with metacognitive strategy, got a higher level than students who applied expository learning strategy. It shows interaction between the type of learning as well as initial statistical knowledge with the escalation of the ability of statistical reasoning. Brain-based learning with metacognitive strategy facilitates the process of conflict, discovery, social interaction, and reflective processes of students. Therefore, students abilities of statistical reasoning are better than expository learning strategy.